Analysis of air permeability and WVTR characteristics of highly impermeable novel rubber nanocomposite. (21st January 2015) - Kumar, S; Chattopadhyay, S; Sreejesh, A; Nair, Sujith; Unnikrishnan, G; Nando, G B
Abstract: This work focuses on analyzing the barrier properties of novel Bromobutyl (BIIR)- Polyepichlorohydrin (CO) rubber nanocomposites and developing a unique model to ease the understanding of the water vapor transmission rate (WVTR) properties. Air permeability, WVTR and morphology of BIIR-CO nanocomposites were investigated and compared with the standard BIIR vulcanizate. From the morphological studies using AFM imaging technique and HR-TEM measurements, the developed BIIR-CO nanocomposites were considered to have a mostly intercalated structure. However, the dispersion of the nanoclay in the composites was very good. Air permeability of BIIR-CO nanocomposites decreased dramatically by 64% as compared to that of the standard BIIR vulcanizate. Considerable reduction in WVTR up to 25% was also achieved for BIIR-CO nanocomposites. Attempts were made to fit the experimental data of the relative gas permeability of nanocomposites with various models predicted earlier. It was observed that the nanoclay orientation ranged from perfect to random, which was decisive in improving the gas barrier properties. A basic model has been developed to predict the water vapor ingress by considering the polarity factor along with tortuosity factor which has been presented schematically. It reiterates the dependency of water vapor ingress on the polarity of the BIIR-CO rubber nanocomposites.